Understanding Consumer Purchase Decisions on TikTok Shop: The Role of Digital Trust Mediation in Live Streaming and Customer Engagement - Yasir Hudzaifah; Joko Susilo (ICON Publisher, 2026)
The rapid growth of social commerce has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing strategies through live streaming platforms such as TikTok Shop. This study aims to analyze the effect of live streaming and customer engagement on purchase decisions with digital trust as a mediating variable among TikTok Shop users. This research employed a quantitative approach using explanatory research design. Data were collected through online questionnaires distributed to 150 respondents who had purchased MSME products through TikTok Shop live streaming. The sampling technique used purposive sampling. Data analysis was conducted using Structural Equation Modeling-Analysis of Moment Structure (SEM-AMOS) with AMOS 21 software. The results showed that live streaming and customer engagement had a positive and significant effect on purchase decisions. In addition, live streaming and customer engagement were also proven to significantly influence digital trust. Digital trust had a positive and significant effect on purchase decisions and successfully mediated the relationship between live streaming and customer engagement toward purchase decisions. These findings indicate that digital trust plays a strategic role in strengthening the effectiveness of social commerce marketing on TikTok Shop. This study contributes theoretically to the development of digital marketing and social commerce literature, particularly regarding the mediating role of digital trust in online consumer behavior. Practically, the findings provide recommendations for MSMEs to optimize interactive live streaming, increase customer engagement, and strengthen consumer trust to improve purchase decisions in digital commerce platforms.